Sacral stress fractures in long-distance runners - Major, N. M.; Helms, C. A. (American Journal of Roentgenology, 2000)
OBJECTIVE: Sacral stress fractures in athletes are rare but important to recognize because the symptoms often mimic sciatica and can lead to delay in diagnosis and treatment. The radiographic findings are characteristic and can facilitate early diagnosis and lead to appropriate treatment. CONCLUSION: The clinical presentation of runners with sacral stress fractures can mimic disk disease. However, stress fractures in athletes, especially long-distance runners, must be treated differently. The imaging characteristics appear as linear abnormal signal intensity paralleling the sacroiliac joint on MR imaging and linear sclerosis with cortical disruption on CT. Imaging with bone scintigraphy shows increased uptake that parallels the sacroiliac joint.